Creative Arabic Learning through Student-Made Storytelling: A Constructivist Approach in Malaysian Islamic Schools - Baharun, Segaf; Hanifansyah, Nur; Salsabil, Aufa Hanin (Arabi : Journal of Arabic Studies, 2025)
This study explores the implementation of student-made storytelling as a constructivist approach to enhance Arabic language learning among secondary students in Kedah, Malaysia. Thirty students aged 15–16 participated in a six-week program involving story creation, writing, and performance in Arabic. Using a mixed-methods design, data were collected through pre–post language tests, classroom observations, interviews, and student journals. Results showed significant improvement in speaking and writing skills, especially in vocabulary richness, narrative coherence, and communicative confidence. Qualitative findings indicated that storytelling increased students’ creativity, intrinsic motivation, and emotional engagement with the Arabic language. The study concludes that student-made storytelling provides a transformative learning experience that unites linguistic, cognitive, and moral dimensions. It offers a practical framework for Islamic schools to promote creative, meaningful, and spiritually grounded Arabic education.